Peningkatan Literasi Membaca pada Siswa Sekolah Dasar melalui Program Rumah Cerdas Calistung dalam Program KKN Desa Buniwangi: Pengabdian - Linda Hindriana; Rayhan Fadhlan Andani; Adinda Aulia; Dede Siti Nurjanah; Ilmi Siti Najmah Alfaujiyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Smart CALISTUNG House program, initiated during the Kuliah Kerja Nyata (KKN) in Buniwangi Village, was established to address the low reading literacy skills among elementary school students. This qualitative research, employing a case study approach, aims to describe the program's implementation and analyze its impact on enhancing students' reading literacy. Data were collected through participatory observation, in-depth interviews with program facilitators, teachers, parents, and students, and document analysis. The findings indicate that the learning activities at the Smart CALISTUNG House, which applied enjoyable and personalized methods, successfully: (1) Increased students' interest in reading and learning motivation; (2) Strengthened letter and syllable recognition, as well as reading fluency; (3) Built children's self-confidence. The main supporting factors were the comfortable, non-formal learning atmosphere, the tutors' patient approach, and strong community support. It is concluded that this program is an effective and contextual model for improving basic literacy skills. It also serves as a potent community empowerment vehicle for supporting children's education at the village level.